To what extent can a critical literacy intervention develop Grade 3 children’s capacity to (re)read and (re)write fairytale texts from a critical perspective? - Ahmed, Aqeela (My University, 2024)
In South Africa critical literacy is evident in Literacy lessons in higher grades of schooling but are lacking in the lower grades. This study explores an intervention in which I attempted to implement critical reading and writing with young children. It aims to worthily fill a gap in the field of research pertaining to critical literacy with young children in South Africa. This research study investigated to what extent a critical literacy intervention can develop Grade 3 children’s capacity to (re)read and (re)write fairytale texts from critical perspectives. In addition, the study explores what the texts produced by Grade 3 learners show about their developing criticality, and the obstacles and limitations to developing their ability to engage critically with texts. 28 children from an ex-model C school in Johannesburg participated in this study. The study followed a qualitative approach where children deconstructed and (re)read fairytale texts and then reconstructed and (re)designed them. The data collected from class discussions, role plays and written work was analysed using thematic content analysis and thick description. The findings show that the role of the teacher, alternative texts and the affordances of the performative mode had a significant impact on the success of learners’ capacity to (re)read and (re)write fairytale texts from a critical perspective. However, the learners’ uptake of critical literacy was uneven and not linear. While the learners’ collaborative performances showed signs of emerging criticality, many of them reverted to dominant discourses in the individual, written mode.
A research report submitted in partial fulfilment of the requirements for the degree Master of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023
Keywords: Critical literacy; Grade 3 children; Young children